2017
DOI: 10.2105/ajph.2016.303628
|View full text |Cite
|
Sign up to set email alerts
|

Public Health, Ethics, and Autonomous Vehicles

Abstract: ). Reprints can be ordered at http://www.ajph.org by clicking the "Reprints" link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(79 citation statements)
references
References 15 publications
0
68
1
2
Order By: Relevance
“…Manufacturers are increasingly vulnerable to reputational risks imposed by accidents associated with failures in design and manufacturing (Hevelke & Nida-Rümelin, 2015;Tien, 2017). The current legal frameworks also do not define the practical and moral responsibilities of software programmers in designing "crash algorithms" that determine life or death decisions, raising numerous concerns over AVs' implications on public ethics (Fleetwood, 2017;Pinsent Masons, 2016). Governments have yet to address whether algorithms' decision-making criteria during accidents should be standardised.…”
Section: Liabilitymentioning
confidence: 99%
“…Manufacturers are increasingly vulnerable to reputational risks imposed by accidents associated with failures in design and manufacturing (Hevelke & Nida-Rümelin, 2015;Tien, 2017). The current legal frameworks also do not define the practical and moral responsibilities of software programmers in designing "crash algorithms" that determine life or death decisions, raising numerous concerns over AVs' implications on public ethics (Fleetwood, 2017;Pinsent Masons, 2016). Governments have yet to address whether algorithms' decision-making criteria during accidents should be standardised.…”
Section: Liabilitymentioning
confidence: 99%
“…Economic incentives of AV purchasers may also motivate manufacturers to design algorithms that discriminate between passengers of publicly-owned AVs and those of privately-owned AVs. Unlike publicly-owned AVs, private AV purchasers may expect their AVs to prioritise their safety over all others [89,92] and thus, AV manufacturers could program their algorithms according to these customer preferences to maximise profits. While doing so ensures AVs' commercial success, as it has been shown that consumers do prefer riding in AVs that prioritise passenger safety [108,109], safety risks would be transferred from users of privately-owned AVs, who benefit from their use, to individuals who cannot afford to purchase AVs.…”
Section: Perverse Incentivesmentioning
confidence: 99%
“…Moreover, the same general type of argument has also been made within the domain of public health research, by Janet Fleetwood. She writes that automated driving is an “incredible invention” likely to “transform transportation” while “saving lives.” For this reason, public health leaders “should welcome” this development (Fleetwood, , p. 536).…”
Section: Part Iii: Crash‐avoidance Strategiesmentioning
confidence: 99%